Bonding and Energy Parameters for Pr and Nd Complexes of benzimidazoles - Mittal, S.; Vyas, P.C.; Oza, C.K. (Asian Journal of Chemistry, 2010)
Complexes of praseodymium (III) and neodymium (III) with benzimidazoles have been synthesized and characterized by their conductance and infrared spectral studies. The values of interelectronic repulsion, i.e. Slater-Condon (F2, F4, F6), Racah (E1, E2, E3) parameters and spin-orbit interaction referred as Lande´ (ζ4f) parameters have been calculated from their electronic spectral data. A comparison of these parameters for the complexes with Pr3+ and Nd3+ free ion parameters is discussed. Using F2 values, the nephelauxetic ratio (β) and. bonding parameter (b1/2) have been calculated. The relative variation of covalent bonding in the complexes has been reported.